Multiple positive solutions of fractional differential equations with improper integral boundary conditions on the half-line - Ning Wang; Zongfu Zhou (Boundary Value Problems, 2023)
Abstract This paper investigates the existence of positive solutions for a class of fractional boundary value problems involving an improper integral and the infinite-point on the half-line by making use of properties of the Green function and Avery–Peterson fixed point theorem. In addition, an example is presented to illustrate the applicability of our main result.